EVALUATION OF POLYPHARMACY IN GERIATRIC PATIENTS PARTICIPATING IN THE CHRONIC DISEASE MANAGEMENT PROGRAM (PROLANIS) - jihan astuti; Salsabilla Wandira1; salma rahmadani; afdhal hanania; kharazi vitonova (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Chronic diseases such as type 2 diabetes mellitus and hypertension remain highly prevalent worldwide, including in Indonesia. The geriatric population is particularly vulnerable because of their susceptibility to polypharmacy, which increases the risk of adverse outcomes. This study aimed to evaluate polypharmacy among geriatric patients, especially participants of the PROLANIS, using a Systematic Literature Review (SLR). A literature search was conducted through Google Scholar following PRISMA guidelines. Of 40 articles identified, only three met the inclusion criteria, consisting of publications from the last 10 years indexed by SINTA and SCOPUS. The review included 350 geriatric patients, most aged ≥60 years and predominantly female. The main chronic conditions were hypertension and diabetes mellitus, with Lisni et al. (2025) specifically reporting type 2 diabetes. Polypharmacy was strongly associated with drug interactions, where moderate-severity combinations such as glimepiride-metformin (18.6%) were most frequent, and pioglitazone-clopidogrel was categorized as high-severity. These interactions mainly increased the risk of hypoglycemia, while others reduced antidiabetic effectiveness. Utaminingrum et al. (2015) emphasized polypharmacy in the broader context of irrational drug use, including self-medication and antibiotic overuse. Factors linked to polypharmacy included the number of prescribed drugs and education level, while age and gender showed no significant associations.